PENGUKURAN LAJU PAPARAN RADIASI DAN EFEKTIVITAS DINDING SERTA PERISAI RADIASI RUANG PANORAMIK - Haekal Ilmi; Dwi Rochmayanti (Perhimpunan Radiografer Indonesia (PARI), 2018)
Background : The panoramic room at Radiological Installation in Sunan Kalijaga Hospital has a room divider in the form of radiation shield with a thickness of 7.5 cm which is visible only in the form of plywood and unknown thickness of lead in it, ideally radiation shield has a thickness equivalent to 2 mm of lead, but the barrier it’s not. The purpose of this study is to determine the value of the exposure rate and the effectiveness of walls and shields in the room. Methods :The method of this research is quantitative, data collected by observing, survey and also documentation. Measurement of the exposure rate is measured at the time of exposure through walls and shields while measuring effectiveness is measured at the time before and after exposure through walls and shields. In order to drawing the conclusion, the data obtained then compared with the Perka No. 8 of 2011 to declare about the room safe or not. At the rate of exposure the limit is 1 mSv / year for the general public and 20 mSv for radiation workers, whereas the effectiveness should not exceed the 5% tolerance. Results : The result of this research reveal that the measurement results of the rate of radiation exposure in the panoramic chamber has an average of 0.0538 mSv/year and is declared safe as it meets the standards. Effectiveness at some points has a tolerance value exceeding the limit, ie 50% door, 16,667% room divider, and 69,766% glasspok, while on the right wall 1.389% and the rear wall 0% both have tolerance values below the limit. Conclusion : Based on these results indicate that the overall measurement of radiation exposure is below the maximum limit. The average value is 0.0538 mSv/year